English Noun Phrase Constructions in the Translated Version of Surah Mary (Maryam) of the Holy Quran - Wahyuni, Hanna Irma; Bram, Barli (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. Noun phrases (NP) are often used in forming sentences in any written work as the subject or object of the sentence. However, less research has been done regarding the use of NP in the English translation of Al-Quran. This paper investigates the patterns of NP in the English translation of Mary (Maryam) of the holy Quran translated by Talal Itani. Employing a descriptive qualitative method, the research analyzed 163 data found from 98 verses of translated Mary Surah (as instrument) syntactically. Three conclusions can be drawn from this study. Firstly, 38 NP patterns appear with the most frequently used NP pattern being determiner+noun 59 times (36.20%). Second, the NPs used were complex (6.75%), 152 simple NPs (93.25%), 97 specific NPs (59.51%), and 66 general NPs (40.49%). Last, some verses are only phrases and not clauses, so 1 verse consists of 1 complex NP. The implication of this finding will help EFL learners and prospective teachers understand the function and patterns of NP in making good English sentences. This study only focuses on identifying NP patterns, future researchers are suggested to research the function of English NP in each verse in the English translation of the Koran. Keywords: Al-Quran, Function, Mary, Noun Phrase (NP), Pattern, Syntax